Signaling an Outside Option - Susanne Ohlendorf; Patrick Schmitz (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
We consider the case of an upstream seller who works to improve an asset that has been specialized to a downstream buyer's needs. The buyer then makes a take it or leave it offer to the seller about how the future surplus should be split. We assume that the seller from the outset has private information about the fraction of the surplus that he can realize on his own, and show that this leads to higher investment compared to the complete information case. This positive effect on investment is countervailed by the occurrence of inefficient separations, which result when the buyer mistakenly tries to call the seller's bluff with a low offer.
urn:nbn:de:bvb:19-epub-13273-5
Keywords: D82; 330; signaling; relationship-specific investment; incomplete contracts; outside options